How to build a business rules engine : extending application functionality through metadata engineering - Chisholm, Malcolm, 1953- (Morgan Kaufmann series in data management systems., 2004)
This is the only book that demonstrates how to develop a business rules engine. Covers user requirements, data modeling, metadata, and more. A sample application is used throughout the book to illustrate concepts. The code for the sample application is available online at http://www.refdataportal.com. Includes conceptual overview chapters suitable for management-level readers, including general introduction, business justification, development and implementation considerations, and more. This is the only book that demonstrates how to develop a business rules engine. Covers user requirements, data modeling, metadata, and more. A sample application is used throughout the book to illustrate concepts. The code for the sample application is available online at http://www.refdataportal.com. Includes conceptual overview chapters suitable for management-level readers, including general introduction, business justification, development and implementation considerations, and more.